Virtual vs. Traditional Environments and Their Influence on Students’ Listening Performance in a Foreign Language – A Case Study in Albania - Pema, Olsa (European Journal of Multidisciplinary Studies, 2017)
The essential role of the listening competence in Second Language Teaching, and the new rhythm of advancement in the new Internet epoch call for a paradigmatic reform of teachers’ roles, contents and functions in teaching listening skill in order to guarantee a successful forward-looking process. Considering this context, this study highlights an innovative academic experience in Albania consisting of a special class website integrated in teaching English listening skills to Albanian university students as well as creating and implementing a demanding listening curriculum at an FCE level; this project and the analysis of its results follow a comparative approach at all stages. This paper aims at examining the efficiency of website compared with traditional means of teaching listening in English, by analyzing and assessing the difference between the level of the experimental group’s performance and that of the control group during the listening practice. The actual comparison of results, which involves the assessment of their scores in two special tests, one taken before the project and one after its completion, shows that both learning environments have their merits in helping them progress with their listening competence. However, the amount of progress made by the students of the two groups is not identical, as there is a significant difference in favour of the experimental group, which, as our statistical analysis carried out by the help of the SPSS program shows, is ample proof of the advantage that the use of websites brings to the process of developing one’s listening competence in a foreign language.